Altered Fecal Microbiota Composition in Older Adults With Frailty - Xu, YuShuang; Wang, YiHua; Li, HeWei; Dai, Yong; Chen, Di; Wang, MengMeng; Jiang, Xin; Huang, ZaoZao; Yu, HongLu; Huang, JuanJuan; Xiong, ZhiFan (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: Frailty is a common geriatric syndrome that is diagnosed and staged based mainly on symptoms. We aimed to evaluate frailty-related alterations of the intestinal permeability and profile fecal microbiota of healthy and frail older adults to identify microbial biomarkers of this syndrome. Methods: We collected serum and fecal samples from 94 community-dwelling older adults, along with anthropometric, medical, mental health, and lifestyle data. Serum inflammatory cytokines IL-6, HGMB1, and intestinal permeability biomarker Zonulin were measured using enzyme-linked immunosorbent assays. The 16S rRNA amplicon sequencing method was performed to determine the fecal composition of fecal microbiota. We analyzed the diversity and composition differences of the gut microbiota in the two groups and assessed the relationship between the changes in microbiota structure and clinical biomarkers. Results: Older adults with frailty showed higher concentrations of IL-6, HGMB1, and Zonulin. Although there were no statistically significant differences in the diversity index and evenness indices or species richness of fecal microbiota between the two groups, we found significant microbiota structure differences. Compared with the control group, fecal samples from the frail group had higher levels of the Akkermansia, Parabacteroides, and Klebsiella, and lower levels of the commensal genera Faecalibacterium, Prevotella, Roseburia, Megamonas, and Blautia. Spearman’s correlation analysis showed that the inter-genus interactions were more common in healthy controls than older adults with frailty. Escherichia/Shigella, Pyramidobacter, Alistipes, and Akkermansia, were positively correlated with IL-6, while Faecalibacterium, Prevotella, and Roseburia were negatively correlated with IL-6. Alistipes were found to be positively correlated with HGMB1. Akkermansia and Alistipes were linked to the increased serum level of inflammatory factors and intestinal permeability. Conclusions: Frailty is associated with differences in the composition of fecal microbiota. These findings might aid in the development of probiotics or microbial-based therapies for frailty.